Is an educational intervention effective in improving the diagnosis and management of suspected ectopic pregnancy in a tertiary referral hospital in South Africa - Wipplinger, Petro (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MMed (Obstetrics and Gynaecology))--University of Stellenbosch, 2010.